HOW MISUSE OF ANTIMICROBIAL AGENTS IS EXACERBATING THE CHALLENGES FACING SOMALIA’S PUBLIC HEALTH - MOUSSA, Ayan Aden; GARBA, Bashiru (African Journal of Infectious Diseases (AJID), 2022)
Background: In contrast to most developed countries, antimicrobial resistance (AMR) has continued to be a serious challenge to public health in the majority of resource-limited countries in Africa. Materials and method: A comprehensive review of all available literature reporting on antimicrobial resistance patterns, antimicrobial drug usage in both human and animals, as well as national AMR regulations in Somalia was undertaken. Results: The review observed that successful AMR control and surveillance among resource-poor nations are affected by a lack of infrastructural and institutional capacities, poor investment in human and material resources, as well as non-adherence to available policies. The humanitarian crisis affecting Somalia has persisted for too long, leading to loss of lives, productivity and dilapidation of public health infrastructures. Somalia like most countries has adopted the One Health approach in developing their soon-to-be gazetted National Action Plan on AMR, which covers both human health, animal health and the environment. Although